Servant Leadership and Organizational Commitment in Female Academics: The Mediating Role of Work-Life Balance - Nezia Arkhindah, Lintang; Tentama, Fatwa; Tarnoto , Nissa (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This teaching staff commitment is a crucial factor influencing the success and continuity of various activities within higher education. This research seeks to develop and evaluate a theoretical model that examines the impact of servant leadership on organizational commitment, with work-life balance serving as a mediating variable for female teaching staff in the higher education sector. Method: The study involved 117 female teaching staff who were permanent staff, married, and had at least one year of experience in higher education. Using a quantitative research design, the researchers employed Structural Equation Modeling (SEM) for analysis. Data collection involved scales measuring organizational commitment, servant leadership, and work-life balance. The validity and reliability of the constructs were assessed using an outer model, and the research data were analyzed using an inner model in SmartPLS 4.0. Results: The study findings demonstrate the development of a theoretical framework illustrating the impact of servant leadership on organizational commitment, with work-life balance serving as a mediating variable, consistent with the empirical evidence. However, the results indicate that the relationship between servant leadership and organizational commitment cannot be explained by work-life balance acting as a mediator. Novelty: This study introduces a new approach by simultaneously testing a mediator involving the variables of organizational commitment, servant leadership, and work-life balance, with a special focus on female teaching staff who work and are married in a university environment.